The Effect Of The Project Based Learning (PJBL) Model On Students' Creative Thinking Abilities In The Subject Of Science Class IV - Opranti, Swi Halizah; Simamora, Aprido B.; Sibarani, Imelda Sabrina (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to determine the effect of the Project Based Learning (PjBL) model on students’ creative thinking skills in the Science and Social Studies (IPAS) subject for fourth-grade students at SD Negeri 124394 Pematangsiantar. This research employed a quantitative method with a One Group Pretest-Posttest design. The participants were 23 fourth-grade students. The research instrument consisted of six essay questions validated by experts. Data were analyzed using the N-Gain test to measure the improvement in creative thinking skills. The results showed a significant increase in students’ creative thinking skills after the implementation of PjBL, with the average pretest score of 35.95 rising to 84.60 in the posttest. The N-Gain calculation indicated a high category with an average score of 0.72 (72.18%). Thus, thePjBL model has a positive effect on enhancing students’ creative thinking skills in IPAS subject